Extract Ethanol of Tempuyung (Sonchus arvensis) Leaves as Anti-Hyperuricemia: In Vitro Studies - Parisa, Nita; Hidayat, Rachmat; Fatmawati, Fatmawati (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2024)
Hyperuricemia is a condition where there is an increase in blood uric acid levels above 7 mg/dL in men and 6 mg/dl in women. One of the enzymes that plays a role in hyperuricemia is xanthine oxidase which can inhibit uric acid synthesis. Tempuyung leaves (Sonchus avernis) are one of the plants that have antihyperuricemia properties. This study aims to determine the effect of ethanol extract of tempuyung leaves on xanthine oxidase in vitro. Tempuyung leaves come from Palembang, South Sumatra, Indonesia, and are macerated with 96% ethanol until a thick extract is obtained. The xanthine oxidase inhibition test was carried out on tempuyung leaf extract and Allopurinol with respective concentrations of 6.25; 12.5; 25; and 50 ppm and followed by absorption measurements using UV-V spectrophotometry at a wavelength of 293 nm and determining the IC50 value. The research results showed that the ethanol extract of daun tempuyung leaves had an IC50 value of 23.37 ppm, higher than allopurinol of 17.16 ppm which was used as a reference. These results classify the ethanol extract of daun tempuyung leaves as a strong inhibitor of the xanthin oxidase enzyme. Therefore, the ethanol extract of daun tempuyung leaves has the potential to be anti hyperuricemic.